Answer:
f(x) = cos(x) / (2+sin(x))
Step-by-step explanation:
You gotta use u-substitution. You probably only heard of u-sub from integration, but you can also use it on derivatives as well.
f(x) = ln(2+sin(x))
I let u=2+sin(x)
So now my new equation is
f(u) = ln(u)
you already know the derivative of ln(u), it's 1/u, but you also gotta multiply it by u' because of the chain rule. So the new equation is
f'(u) = 1/u * u'
substitute your x-values back in to get your answer.
f(x) = cos(x) / (2+sin(x))